Bugs! Bugs! Bugs! - Jennifer Dussling; Nang ChanYeema (New York, USA DK Publishing, Inc., 1998)
Describes the hunting activities of various bugs, including the praying mantis, wood ant, and dragonfly.
Keywords: Level Books